Combining hyperspectral imaging and electrochemical sensing for detection of Pseudomonas aeruginosa through pyocyanin production. Issue 4 (24th June 2022) - Dunphy, R. David; Lasserre, Perrine; Riordan, Lily; Duncan, Katherine R.; McCormick, Christopher; Murray, Paul; Corrigan, Damion K.
Abstract : Pyocyanin production by Pseudomonas aeruginosa can be monitored using hyperspectral imaging and square wave voltammetry, with electrochemical impedance spectroscopy offering new avenues for low-cost sensing approaches to biofilm characterisation. Abstract : Despite bacterial biofilms representing a common form of infection, notably on medical devices post implantation, their detection and characterisation with existing methods is not sufficient to inform clinicians about biofilm presence or treatment response in affected patients. This study reports the development and use of a combined hyperspectral imaging (HSI) and electrochemical platform to monitor biofilm formation optically and electrochemically. Firstly, production of pyocyanin, a common pigmented and redox active secondary metabolite produced by P. aeruginosa, is monitored by combined HSI and square-wave voltammetry. Secondly, P. aeruginosa biofilm formation is characterised directly using electrochemical impedance spectroscopy. This suite of optical and electrochemical measurements allows for combined monitoring of secondary metabolite/virulence factor production along with direct monitoring of biofilm formation on the sensor surface. Crucially, the easy to deploy and low-cost nature of the selected sensing technologies means the approach can be developed for enhanced study of biofilms and/or at the point of care.